Human Disturbances of Denning Polar Bears in Alaska - Amstrup, Steven C. (ARCTIC, 1993)
Polar bears (Ursus maritimus) give birth in dens of snow and ice. The altricial neonates cannot leave the den for >2 months post-partum and are potentially vulnerable to disturbances near dens. The coastal plain (1002) area of Alaska's Arctic National Wildlife Refuge (ANWR) lies in a region of known polar bear denning and also may contain >9 billion barrels of recoverable oil. Polar bears in dens could be affected in many ways by hydrocarbon development, but neither the distribution of dens nor the sensitivity of bears in dens has been known. I documented the distribution of dens on ANWR between 1981 and 1992 and observed responses of bears in dens to various anthropogenic disturbances. Of 44 dens located by radiotelemetry on the mainland coast of Alaska and Canada, 20 (45%) were on ANWR and 15 (34%) were within the 1002 area. Thus, development of ANWR will increase the potential that denning polar bears are disturbed by human activities. However, perturbations resulting from capture, marking, and radiotracking maternal bears did not affect litter sizes or stature of cubs produced. Likewise, 10 of 12 denned polar bears tolerated exposure to exceptional levels of activity. This tolerance and the fact that investment in the denning effort increases through the winter indicated that spatial and temporal restrictions on developments could prevent the potential for many disruptions of denned bears from being realized.Key words: Alaska, ANWR, Arctic, denning, disturbance, impact, oil development, polar bear, reproduction, Ursus maritimus Les ourses polaires (Ursus maritimus) donnent naissance à leurs petits dans des tanières de neige et de glace. Les nouveau-nés nidicoles ne peuvent quitter la tanière avant au moins deux mois suivant leur naissance, et des perturbations près de leur tanière sont susceptibles de les affecter. La région de la plaine côtière (1002) du Arctic National Wildlife Refuge (ANWR) en Alaska est située dans une zone connue comme site de mise bas pour l'ourse polaire et qui pourrait ...